Pest identification in sugarcane crop using acoustic sensor - Durgaprasadarao, P.; Srinivas, M. (International Journal of Engineering and Technology, 2019)
In the existing system, the disease in sugarcane crop is found manually. So there are more chances for loses to the farmers. Now a dayâ€™s agriculture growth is reducing because of more pollution and pest in the environment. In India most of the farmers grow sugarcane but are not getting good yields due to bugs and larvae in sugarcane. To avoid this situation, the proposed design has been developed with acoustic sensor and MQ2 sensor. In this proposed design system used aurdino for monitoring the noise and ammonium gas. So finding the problem can be simplified and can be solved easily.Â Â